The reform of papal’s institutions for social communication - KAMIŃSKI, RAFAŁ (Prawo Kanoniczne, 2017)
With the advent of a new medium which became the film and the spread of the cinematography all around the world, in the Church there was an increase of awareness and the need to take an interest in new technologies and to create within the framework of the Holy See the institutional protection of worshippers against the harmful impact of inappropriate content, as well as to propagate the useful content. For this purpose, over the years the special institutions were created, which in the structure of the Roman Curia were directly engaged in the media issues. Initially this task was undertaken by the Pontifical Commission, which for several years was subject to constant change (from 1948 to 1964), while from 1964 till 2015 we had to deal with the activities of the Pontifical Council for Social Communications. The last reformatory accent in this field is the appointment by Pope Francis on the 27th of June 2015 the Secretariat for Communication. Like the preceding institutions of social communication, it still has to collaborate in the area of the social communication with the Secretariat of State, uniting together all the media institutions of the Holy See.